1996
DOI: 10.1017/s0079497x00002747
|View full text |Cite
|
Sign up to set email alerts
|

Where Eagles Dare: the Iron Age of Norfolk

Abstract: A survey is presented of the Iron Age in Norfolk, the area containing the heartland of the tribal territory of the Iceni during the Late Iron Age. It makes use of new information from prolific artefact finds from recent excavations and fieldwork, and employing unpublished data from the county Sites and Monuments Record. Settlement evidence and artefact distributions are analysed and used to construct a model for the development of settlement from the Early Iron Age to the Boudican rebellion of AD 60-61. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, rather than seeing decoration as having a specific role which can be undertaken equally well by decorated metal artefacts or pots, which can be interchanged depending on region and time period, my argument is that decorated pottery, bone, and metalwork can all be produced at the same time so long as there is a cultural need. So, in Norfolk in the 2nd and 1st centuries BC, identity was signalled through the use of decorated horse-gear and related paraphernalia and the wearing of torcs (Hutcheson 2004;Davies 1996). However, the reason pottery was not also decorated is not necessarily because the role of decoration was already taken by the metalwork.…”
Section: Discussionmentioning
confidence: 99%
“…However, rather than seeing decoration as having a specific role which can be undertaken equally well by decorated metal artefacts or pots, which can be interchanged depending on region and time period, my argument is that decorated pottery, bone, and metalwork can all be produced at the same time so long as there is a cultural need. So, in Norfolk in the 2nd and 1st centuries BC, identity was signalled through the use of decorated horse-gear and related paraphernalia and the wearing of torcs (Hutcheson 2004;Davies 1996). However, the reason pottery was not also decorated is not necessarily because the role of decoration was already taken by the metalwork.…”
Section: Discussionmentioning
confidence: 99%
“…55 The study of Norfolk during this period has been enhanced by the large number of metal-detected finds that have been incorporated into the archaeological record over the last five years. Davies 1996. Roman tribal centres for the Iceni has been suggested at Caistor St Edmund, Thetford, and Snettisham. Saham Toney is interpreted as another such centre, 56 with evidence for an early military presence also found.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is published with the aid of a grant from English Heritage 91 Gregory 1991, 143. 92 Davies 1996.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…A small number of other excavated barrow burials of this era also feature faience beads, another characteristic 'Wessex' trait. John Davies has identified 13 putative Iron Age burials or other deposits containing human bone (Davies 1996), although the dating of some of these finds may be open to question. Dr Helen Bamford (in Ashwin & Bates in press) has suggested that the presence of faience in this grave indicates a date no earlier than c. 1300 BC.…”
Section: Barrows and Burialsmentioning
confidence: 99%
“…The fact that this is an issue in British prehistoric studies extending beyond the Neolithic and the Bronze Age into the Iron Age as well is emphasised in a number of current publications (Davies 1996;Hill 1995). Part of the answer to this lies in the continuing importance of lessening the dominance of the much-studied yet ultimately untypical Wessex landscape over British prehistory.…”
Section: Territorial Boundaries and Formal Landscape Divisionmentioning
confidence: 99%